Implementasi Sistem Helpdesk Ticketing dalam Penyampaian Permasalahan Terkait Hardware dan Software Menggunakan Model Rapid Application Development Berbasis Web - Hadi Zakaria; Dede Muhar Ardiansyah (Teknik Informatika Universitas Pamulang, 2022)
PT. Intecs Teknikatama Industri is a company engaged in the sale and installation of lubrication equipment. In its operations PT. Intecs Teknikatama Industri has several divisions, one of which handles various problems related to hardware and software. In managing these problems PT. Intecs Teknikatama Industri still uses manual recording, which still often encounters problems between technicians such as inaccurate presentation which results in inefficient reporting. In overcoming this problem, the author conducted research to create a web-based helpdesk ticketing system application using the Rapid Application Development (RAD) method. In an effort to solve this problem, the IT division uses a numbering system (request ticket) that relates to inquiries and technical services as well as complaints regarding the use of hardware or software devices. In this study the authors used a programming language, namely Hypertext Preprocessor (PHP), as well as a MySQL database as a repository for employee complaint data and the Rapid Application Development (RAD) Model in making the design flow. It is hoped that this employee helpdesk ticketing system can simplify the process of submitting problem reports and checking the status of information reports that can assist the IT division in processing employee problem submission data, and can respond to problems efficiently to employees of PT. Intecs Teknikatama Industri.